Students’ Pseudo-Thinking Process in Solving Mathematics Problems in Terms of Learning Style - Nurmaela, Asri Ika; Wahyuni, Indah; Tehtae, Sareef (FKIP Universitas Lampung, 2024)
Pseudo-thinking occurs when students believe something is true or false when it is not entirely true or false. This research aims to study students' pseudo-thinking process in solving mathematics problems in terms of learning styles. Data was obtained using learning-style questionnaire instruments, written tests, and interviews. The method of data analysis applied in this study used the Miles and Huberman model. These research’ outcomes demonstrate that 1) students with visual learning styles in solving mathematics problems are more about remembering what they have seen, such as looking at books and blackboards, visual students experience pseudo-true and pseudo-false, 2) students with auditory learning styles in solving mathematics problems are more about remembering what they hear, such as listening to explanations from the teacher, auditory students experience pseudo-false, and 3) kinesthetic learning style students in solving mathematics problems are more about remembering from people's examples and then practicing and remembering how to do it before, kinesthetic students experience pseudo-false. Keywords: pseudo thinking, solving mathematics problems, learning styles. DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp601-619